Hybrid causal logic model for estimating the probability of an icebreaker–ship collision in an ice channel during an escort operation along the Northeast Passage - Xu, Sheng; Kim, Ekaterina (Ocean Engineering, 2023)
Under severe Arctic ice conditions, escort operations are the most efficient methods for facilitating shipping. Nevertheless, escort operations are among the most dangerous operations, as they may result in icebreaker–ship collisions and/or ship besetting in ice. To mitigate the risk of collisions, it is essential to understand the event sequences of collisions and the risk control options that can be implemented to reduce the occurrence of undesired events. This paper proposes a hybrid causal logic model to estimate the likelihood of an icebreaker–ship collision while considering human factors during an escort operation along the Northeast Passage. The model relies on inputs from four icebreaker captains. Its applicability is demonstrated for a 2018 summer voyage of a cargo ship assisted by an icebreaker. Risk control options are then proposed based on qualitative and sensitivity analyses of the model. The results of this study can assist shipping companies to better understand the sequence of events prior to icebreaker–ship collisions during escort operations in ice-covered waters. This paper provides information on risk reduction measures. In addition, the proposed model can assist in route planning. publishedVersion